Recurrence Patterns After Surgical Resection of Gastroenteropancreatic Neuroendocrine Tumors: Analysis From the National Comprehensive Cancer Network Oncology Outcomes Database. Issue 4 (April 2021) - Chan, Hilary; Zhang, Li; Choti, Michael A.; Kulke, Matthew; Yao, James C.; Nakakura, Eric K.; Bloomston, Mark; Benson, Al B.; Shah, Manisha H.; Strosberg, Jonathan R.; Bergsland, Emily K.; Van Loon, Katherine
Abstract : Objective: Current National Comprehensive Cancer Network guidelines for gastroenteropancreatic neuroendocrine tumors (GEPNETs) recommend complete (R0) surgical resection of the primary tumor and metastases, if feasible. However, large multicenter studies of recurrence patterns of GEPNETs after resection have not been performed. Methods: Patients 18 years or older who presented to 7 participating National Comprehensive Cancer Network institutions between 2004 and 2008 with a new diagnosis of a small bowel, pancreas, or colon/rectum neuroendocrine tumor (NET) and underwent R0 resection of the primary tumor, and synchronous metastases, if present, were included in this analysis. Descriptive statistics and Kaplan-Meier estimates were used to calculate recurrence rates and time-associated end points, respectively. Results: Of 294 patients with GEPNETs, 50% were male, 88% were White, and 99% had Eastern Cooperative Oncology Group performance status 0 to 1. The median age was 55 years (range, 20–90). The median follow-up time from R0 resection was 62.1 months. Recurrence rates were 18% in small bowel NETs (n = 110), 26% in pancreatic NETs (n = 141), and 10% in colon/rectum NETs (n = 50). The frequency of surveillance imaging was highly variable. Conclusions: R0 resection was associated with variable risk of recurrence across subtypes. Further research to inform refinement of guidelines for the appropriate duration of surveillance after R0 resection is needed.